THE IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL ON ISLAMIC EDUCATIONAL LEARNING AT MAMUJU, WEST SULAWESI - A. Misbariani; Baharuddin Baharuddin; Muh. Rapi (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This article discusses the implementation of the problem based learning outcomes model in Islamic religious education learning at Senior High School (SMA) Negeri 2 Kalukku, Mamuju. The results showed that the Problem Based Learning model in Islamic Religious Education learning at SMA Negeri 2 Kalukku, Mamuju Regency, was as follows:  Planning the Problem Based Learning model in Islamic Religious Education learning was guided by the syllabus, lesson plans, learning objectives, learning methods and media, learning tools and resources which are an integral part that cannot be separated from all learning planning stages. Implementation of Problem Based Learning models, has met the standard Problem Based Learning model, educators have taken steps to learn by using the Problem Based Learning model in the field of study of Islamic Religious Education, and Assessment of learning outcomes consisting of attitude and knowledge assessment has been carried out well, but in terms of skills assessment it has not been able to be fulfilled properly.